(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things (IoT) is a system of interrelated computing devices. IoT involves mechanical and digital machines, objects, animals or people that are indicated with unique identifiers and the ability to transfer data over a network without requiring human-to-human as well as human-to-computer interaction. Government of Malaysia in 2015 has introduced the National Internet of Things Strategic Road Map as a way to provide the backbone of modern and smart cities as well to sustain the economic growth. However, the factors influencing IoT readiness in Malaysian organization needs to be further investigated. The purpose of this study is to investigate, identify and propose the readiness factors of IoT implementation. A survey involving a distribution of questionnaire to 30 respondents to get a descriptive indication coupled with interviews with 5 key expert employees from relevant agencies were executed. As a result, there are five factors being proposed and validated descriptively to influence the readiness of implementing IoT in Malaysia. These factors are Human Perspective, Technology Perspective, Governance and Management Perspective, Security Perspective and Policy and Law Perspective. For future work, this study suggest to include more participants using power statistics, hypothetical model testing and expand the questionnaire to other organization in order to develop a more comprehensive result ofIoT readiness in Malaysia.